International Emigrant Selection on Occupational Skills - Alexander Patt; Jens Ruhose; Simon Wiederhold; Miguel Flores (Institute of Labor Economics (IZA), 2017)
We present the first evidence that international emigrant selection on education and earnings materializes through occupational skills. Combining novel data from a representative Mexican task survey with rich individual-level worker data, we find that Mexican migrants to the United States have higher manual skills and lower cognitive skills than non-migrants. Conditional on occupational skills, education and earnings no longer predict migration decisions. Differential labor-market returns to occupational skills explain the observed selection pattern and significantly outperform previously used returns-to-skills measures in predicting migration. Results are persistent over time and hold within narrowly defined regional, sectoral, and occupational labor markets.
Keywords: F22; O15; J61; J24; 330; selection; international migration; skills; occupations